Unaffectionate Fathers in American Literature: A Comparative Study of the Characters of Ephraim Cabot and Dr. Adler - Fatema Sharmina; Md. Joynul Abedinb (Lembaga Sembilan Tiga Community, 2021)
In the study of American literature, the social reality is reflected; the influence of capitalism is seen with its full might. Individualism and capitalism claimed to be movable factors that influence the direction of human attitude as they are pursuing materialistic goals for self-fulfilment. The severity that is found in the construction of the families is portrayed in the literary works. Saul Bellow’s Seize the Day and O’Neill’s Desire Under the Elms have depicted father characters obsessed with their material possession and always obsessed with the fear of losing capital in the long run. These depictions of fathers’ figures are the opposite of the image of fathers that we have in our minds. Here, the fathers are not afraid of their sons for being tyrannical, imbalanced and ill-mannered individuals but are reluctant to treat them even as successors. They are in fear of being claimed financial support or the property by their sons. They consider their sons’ rivals and chased them away because they failed to fulfil the fathers’ roles as expected. This paper analyses and examines the reason behind the behavioural changes and the forces that shape the characters’ natural conduct.